Global tracking passivity-based PI control of bilinear systems: Application to the interleaved boost and modular multilevel converters. (October 2015) - Cisneros, Rafael; Pirro, Matteo; Bergna, Gilbert; Ortega, Romeo; Ippoliti, Gianluca; Molinas, Marta
Abstract: This paper deals with the problem of trajectory tracking of a class of bilinear systems with time-varying measurable disturbance, namely, systems of the form x ̇ ( t ) = [ A + ∑ i u i ( t ) B i ] x ( t ) + d ( t ) . A set of matrices { A, B i } has been identified, via a linear matrix inequality, for which it is possible to ensure global tracking of (admissible, differentiable) trajectories with a simple linear time-varying PI controller. Instrumental to establish the result is the construction of an output signal with respect to which the incremental model is passive. The result is applied to the Interleaved Boost and the Modular Multilevel Converter for which experimental results are given. Highlights: The paper deals with the problem of trajectory of a class of bilinear systems with time-varying measurable disturbance. A set of matrices has been identified for which is possible to ensure global tracking of admissible and differentiable trajectories. A simple linear tyme-varying PI controller has been used. The result is applied to the boost and the modular multilevel converter.